2010 IEEE Latin-American Conference on Communications 2010
DOI: 10.1109/latincom.2010.5640976
|View full text |Cite
|
Sign up to set email alerts
|

Effects of topology and mobility in bio-inspired synchronization of mobile ad hoc networks

Abstract: The interest on firefly approaches to the problem of synchronizing the nodes of a wireless ad hoc communication network is rising, because of its efficiency and efficacy. In this paper we show that it is enough to have an indirect interaction among nodes, either spatially (through multi-hop paths), or temporally (through mobility) to achieve synchronism among them. As the interactions among nodes increases, global synchronization emerges faster.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…Synchronization performance was then analyzed according to the number of nodes and optimized according to the tradeoff of the energy efficiency and convergence rate [21]. A technique for synchronizing the timing of separate networks was suggested by using the positions and mobility of the nodes in mobile ad hoc networks [22]. A distributed frequency synchronization technique using a bioinspired algorithm was suggested to solve the problem of multiple frequency offsets in mesh networks wherein multiple nodes have different carrier frequencies [23].…”
Section: Distributed Time Synchronizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Synchronization performance was then analyzed according to the number of nodes and optimized according to the tradeoff of the energy efficiency and convergence rate [21]. A technique for synchronizing the timing of separate networks was suggested by using the positions and mobility of the nodes in mobile ad hoc networks [22]. A distributed frequency synchronization technique using a bioinspired algorithm was suggested to solve the problem of multiple frequency offsets in mesh networks wherein multiple nodes have different carrier frequencies [23].…”
Section: Distributed Time Synchronizationmentioning
confidence: 99%
“…Unlike these methods, nature-inspired time synchronization methods [19][20][21][22][23][24] can achieve synchronization in a distributed and efficient manner regardless of the number of nodes in a large-scale network. Table 1 summarizes the characteristics, advantages, and disadvantages of the conventional synchronization methods and those of the nature-inspired synchronization methods.…”
Section: Comparisons Between Nature-inspired and Conventionalmentioning
confidence: 99%
“…However, when oscillators are mobile, this assumption can be relaxed a little bit. Puerta et al (2010) showed that mobility could not only contribute to faster convergence of a time synchronization process, but also enable oscillators that did not form a connected graph to become synchronized. Namely, when oscillators in the system do not form a connected graph, there are groups of oscillators that are mutually partly connected, but not connected with other groups of oscillators.…”
Section: Mobile Oscillators In Theorymentioning
confidence: 99%
“…However, the results only hold for dense wireless networks with a large number of nodes. Besides forming dense clusters, the synchronization process is also proven to be accelerated by increasing node mobility in a mobile ad hoc network [57].…”
Section: Bio-inspired Studies Formentioning
confidence: 99%